Climate variability and rural livelihoods in the peruvian Andes : Variabilidad climática y diversificación de ingresos de los hogares en los Andes peruanos - Ponce San Román, Carmen María (2020)
This thesis aims to understand some of the effects of changes in intra-seasonal climate variability on household livelihoods in the Peruvian Andes. Concerns about the effects of climate change on the sustainability of Andean agricultural systems and, in general, concerns about the ability of rural households to adapt to increasing climate uncertainty motivate this thesis. The first study focuses on household decisions over crop portfolio diversification as a response to increasing climate variability. The study investigates whether Andean farmers respond by increasing crop diversity (measured by intercropping and crop diversification indices) or by switching to crops that better tolerate diverse environmental conditions. Based on fixed effects models that use a district panel of 1994 and 2012 agrarian censuses, the study finds that households in colder areas (<11˚C during the crop growing season) adapt to increases in climate variability by concentrating their portfolio into more tolerant crops and reducing intercropping (a practice potentially efficient at controlling pest and disease). This effect is especially strong in the Southern region (more indigenous, less integrated to markets). Taking a broader approach, the second study focuses on Andean rural households in general, investigating whether households adapt to increasing climate variability by concentrating more into non-farm income generating activities (relative to farm activities), and whether spatially distant family networks facilitate this adaptive strategy. Six economic outcomes are modeled in this study: non-farm income shares, non-farm working hours share, farm and nonfarm income levels, and farm and non-farm working hours. Based on generalized linear models that use household information representative of rural provinces of the Andean region, the study finds that households adapt differently across the region. While households in the colder areas of the Central and Northern Andes (below 13˚C during the crop growing season) tend to increase non-farm income as climate variability increases, households in the South show no discernible response. The study results suggest that spatially distant family networks facilitate non-farm opportunities to households facing increasing temperature variability in the Central and Southern Andes. This thesis complements previous studies by providing robust and regionally representative evidence on households’ nonlinear response to climate variability. Furthermore, given that Andean households received little-to-no help to adapt to climate change during the period under analysis, this study informs about household autonomous adaptation to climate change and raises concerns on current adaptation responses that may hamper the sustainability of Andean household livelihoods in the face of climate change.